Kooperacja produkcyjna w rolnictwie w latach 1970-1979 - Trzęsowski, Michał (Wydział Prawa i Administracji UAM, 1983)
In spite of many attempts made in the past at accelerating transformations of the system, the Polish agriculure in its major part is still a small scale production sector. This situation results in a need of searching for more effective ways of transformation making a better use of specific features of indivdiual farming. Productive cooperation is undoubtedly answering for that need as it allows a relatively non- conflict linking of growth of production with gradual social transformations in the country. The experience of the last decade seems to be very valuable in this respect. A particular importance of that period is resulting from the distinctive features of adopted concepts of the cooperational developement, both in the aspect of intra- sector and inter-sector relations. A new productive organization emerged in Polish village is the group of individual farmers, acting according to the regulation of partnership. Productive and economic achievements of these groups are unquestionable, yet their effect on account of the high social costs is still relatively small. As far as the intersector Cooperation is concerned, the experience of the seventies is a long step forwards on the way overcoming isolation between the sectors. A limited effect of the cooperation of seventies in the process of stimulating transformations in our agriculture is consequent non on the fallacy of the very concept, but on the unfavorable external conditioning of the developement of agriculture.
Simple cooperation in agriculture in the years of 1970 -1979